Growth performances of Nile Tilapia (Oreochromis niloticus) fed with diet containing fermented grass from buffalo stomach - SINGPA, Bounlam; KANDEE, Thanousinh; CHANTHAKHOUN , Vongpasith; SOUKVONGSAK, Vang (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
The study on Nile Tilapia fed with the grass fermentation in cow stomach diet consisted of 2 parts. The first trial, the proximate compositions of grass fermentation in buffalo stomach such as protein, lipid, fibre, ash and moisture were determined. The second trial, Preparing the diet mixed with 0 (control), 5(GF5) and 10(GF10) percentage of fermented grass from cow stomach for growth performance investigation of Nile Tilapia for 90 days. The first trial result, proximate compositions of grass fermentation in buffalo stomach including protein, lipid, fibre, ash and moisture were 16.90, 0.14, 0.33, 17.27 and 13.25%, respectively. The second trial, diets containing different levels of fermented grass from buffalo stomach with equal 30 percentage of protein were fed on Nile Tilapia for 90 days; final weight, the average increased weights and average daily weight gain of fish in treatment GF10 were highest and significantly different (P<0.05). Therefore, it can be concluded that Nile Tilapia fed with GF10 was suitable for Nile Tilapia culture.